Keniscayaan Fenomena Sinkretis dalam Aktivitas Misioner Gereja - Fiany Priska Kasedu (Marturia, 2023)
AbstractMission gave birth to biblical texts and several texts in the Bible were also used as the basis for mission, this is the view of missiological hermeneutic activists who try to explore in depth the importance of mission for Christianity. Missionary patterns need to be changed from century to century based on the theological phenomena encountered. The essence of the church's mission is the integration of the kingdom of God that Jesus threw away in His ministry. The Kingdom of God is no longer in the understanding where everyone must be a part of Christianity, but rather the impact of the presence of Jesus which is marked by the realization of justice, truth and renewal. Spiritual experience with Jesus Christ today is not only the experience of people who have given themselves to become Christians, but many people who have experienced Jesus Christ in different ways. This fact was realized when the news about Jesus Christ was met with other religions that caused this thought to occur. Jesus Christ who is met with other religious understandings will give birth to a new understanding that works with each other. Abstrak Misi melahirkan teks Alkitab dan beberapa teks dalam Alkitab pun dijadikan landasan misi, demikianlah pandangan pegiat hermeneutik misiologi yang mencoba menelusuri secara mendalam mengenai pentingnya misi bagi kekristenan. Pola bermisi perlu berubah dari abad ke abad berdasarkan fenomena berteologi yang dihadapi. Inti dari misi gereja ialah pengintegrasian kerajaan Allah yang diberitakan oleh Yesus dalam pelayananNya. Kerajaan Allah ini tidak lagi dalam pemahaman di mana semua orang harus menjadi bagian dari kekristenan, tetapi justru dampak dari kehadiran Yesus yang ditandai dengan terwujudnya keadilan, kebenaran dan pembaharuan. Pengalaman spiritual bersama Yesus Kristus saat ini tidak hanya menjadi pengalaman orang-orang yang telah memberi diri menjadi Kristen, tetapi banyak orang telah mengalami Yesus Kristus dalam cara yang berbeda. Kenyataan ini disadari pada saat pemberitaan mengenai Yesus Kristus diperjumpakan dengan keberadaan agama lain yang menyebabkan terjadinya pertukaran pemikiran. Yesus Kristus yang diperjumpakan dengan pemahaman agama lain akan melahirkan sebuah pemahaman yang baru yang saling memperkarya.